CONSTRUCTAL DESIGN APPLIED TO INVESTIGATE THE INFLUENCE OF GEOMETRY ON THE MASS FLOW RATE OF AN INCLINED PASSIVE WALL SOLAR CHIMNEY ATTACHED TO A ROOM - Leão, M. R.; Claudino, T. M.; Isoldi, L. A.; Rocha, L. A. O.; Estrada, E. S. D.; dos Santos, E. D. (Revista de Engenharia Térmica, 2023)
The present work aims to analyze the turbulent flow in an inclined passive wall solar chimney attached to a room, evaluating the influence of its geometry on the thermal performance of the building (measured by the mass flow rate in the chimney exit) by means of Constructal Design. The flow is considered turbulent, incompressible, under natural convection heat transfer, transient and in a two-dimensional domain that simulates a solar chimney attached to a room. Time-averaged conservation equations of mass, momentum, and energy are numerically solved with the finite volume method using the commercial package FLUENT. For closure modeling of turbulence, it is employed the standard k – ε model. Chimney and room areas are the problem constraints. Moreover, the problem is subjected to three degrees of freedom: the ratio between the inlet opening size and chimney height (Hi/Ha) (which is maintained constant in the present investigations, Hi/Ha = 0.05); ratio between the width of inferior base of the chimney and its height (Wg/Ha); and the ratio between the exit air gap and the inferior base widths of the chimney (We/Wg). The latter two degrees of freedom are varied. Results showed that the degrees of freedom analyzed have a strong influence on the mass flow rate of the air in the building, confirming that the geometrical configuration of solar chimney can be important for the improvement of thermal conditions on the attached building.